Teman (Mangosteen Effervescent Tablets) Development and Processing of Mangosteen Peel Extract Into Effervescent as a Health Supplement - Lutfi Sukowati Ilyasa (International Journal Labs, 2023)
Conducting an internal analysis aimed at knowing strengths and weaknesses is important so that the choice of the strategy used is accurate and appropriate. Setting up a framework internally can help grow a business faster and make the business organized and structured. The stages of this research are the stages of business establishment, operational goals and objectives, operation design, delivery of operations and operational cost budgets. HC Strategy is defined as the company's plan to respond to or anticipate external and internal changes in accordance with the Decision Stage (QSPM) and Bussines Level Strategy, namely promoting online and offline so as to improve its position in the competition that is implemented. It can be concluded that this study evaluated the development and processing of mangosteen peel extract into effervescent tablets called TEMAN. These tablets are intended as a health supplement that can help maintain a healthy body through the benefits of the mangosteen peel content contained in it. Therefore, this research can make an important contribution in the development of quality and beneficial health supplements for society.